2021
DOI: 10.12688/wellcomeopenres.16620.2
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the incidence of clinically diagnosed influenza: an England population-based cohort study 2008-2018

Abstract: Background: People of non-White ethnicity have a higher risk of severe outcomes following influenza infection. It is unclear whether this is driven by an increased risk of infection or complications. We therefore aimed to investigate the incidence of clinically diagnosed influenza/influenza-like illness (ILI) by ethnicity in England from 2008-2018. Methods: We used linked primary and secondary healthcare data (from the Clinical Practice Research Datalink [CPRD] GOLD and Aurum databases and Hospital Episodes St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Only 39% (239 194 of 607 087) of individuals with a QRISK2 score of 10% or higher had diagnosed hypertension. Other UK cohort studies have reported increases in the incidence of influenza-like illness to be associated with non-White ethnicity and social deprivation, 22 , 23 both of which are cardiovascular risk factors included in the QRISK2 algorithm and can result in higher QRISK2 scores assigned to individuals with these characteristics.…”
Section: Discussionmentioning
confidence: 96%
“…Only 39% (239 194 of 607 087) of individuals with a QRISK2 score of 10% or higher had diagnosed hypertension. Other UK cohort studies have reported increases in the incidence of influenza-like illness to be associated with non-White ethnicity and social deprivation, 22 , 23 both of which are cardiovascular risk factors included in the QRISK2 algorithm and can result in higher QRISK2 scores assigned to individuals with these characteristics.…”
Section: Discussionmentioning
confidence: 96%